Microbial toxins : molecular and cellular biology. - Proft, Thomas, ....- (Norfolk : Horizon Bioscience, 2005)
In recent years, enormous progress has been made in our understanding of the molecular and cellular biology of microbial toxins. This has important implications for the development of novel therapeutics such as antimicrobial agents, antitoxins, vaccines etc., and is particularly relevant for toxins that have the potential for use in bioterrorism. In addition, toxin research contributes to the understanding of the structures, functions and metabolism of eukaryotic cells in health and disease. Written by leading toxinologists, this topical book comprehensively reviews the molecular and cellular biology of the most important microbial toxins with a focus on recent advances in the field. Topics include: toxin ADP-ribosylation of proteins, toxin inhibition of protein synthesis, modulation of actin cytoskeleton, cytolethal distending toxins, cell-damaging/pore-forming toxins, clostridial neurotoxins, toxins of the immune system, streptococcal and staphylococcal toxins, anthrax toxins, Shiga toxin, Yersinia toxin, mycotoxins, and the regulation of toxin expression. The books concludes with a chapter on the potential of microbial toxins in bioterrorism. Essential reading for everyone with an interest in microbial toxins and recommended reading for other scientists with an interest in bioterrorism, microbial pathogenesis, microbial genomics, antimicrobial agents, and vaccine development.
Keywords: Toxicologie